2013
DOI: 10.3109/21681805.2013.769460
|View full text |Cite
|
Sign up to set email alerts
|

Assessing chronic pelvic pain syndrome patients: Blood plasma factors and cortisol saliva

Abstract: The findings show an immune response extending to the circulatory system, in which MIF makes a significant contribution to CP/CPPS. This study also indicates TNF-α as a circulatory component when excluding subjects with concomitant diseases. Both MIF and TNF-α have previously been highlighted for other diseases related to chronic pain and here also for CP/CPPS. These results provide further insights into the immunological basis of CP/CPPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The pro‐inflammatory cytokine MIF can activate macrophages, inhibit their migration, enhance their phagocytosis, and kill tumor activity, and also play a role in immune‐mediated diseases. Blood plasma levels of MIF and TNF‐α were significantly increased in the CP/CPPS patients . The findings show an immune response extending to the circulatory system, in which MIF makes a significant contribution to CP/CPPS.…”
Section: Cp/cpps Immune Microenvironmentmentioning
confidence: 76%
See 1 more Smart Citation
“…The pro‐inflammatory cytokine MIF can activate macrophages, inhibit their migration, enhance their phagocytosis, and kill tumor activity, and also play a role in immune‐mediated diseases. Blood plasma levels of MIF and TNF‐α were significantly increased in the CP/CPPS patients . The findings show an immune response extending to the circulatory system, in which MIF makes a significant contribution to CP/CPPS.…”
Section: Cp/cpps Immune Microenvironmentmentioning
confidence: 76%
“…Evidence begins to appear, and this connection also exists in neuropathic pain, such as lumbago . The levels of TNF‐α, IL‐1β, IL‐6, and macrophage migration inhibitory factor (MIF) were pathologically altered in long‐term pain subjects . The pro‐inflammatory cytokine MIF can activate macrophages, inhibit their migration, enhance their phagocytosis, and kill tumor activity, and also play a role in immune‐mediated diseases.…”
Section: Cp/cpps Immune Microenvironmentmentioning
confidence: 99%
“…The underlying mechanisms associated with prostate inflammation and anti-inflammation activity remain unclear. Several studies have shown that the proinflammatory factors TNF-α and IL-1β were increased in prostatic fluid, seminal plasma, or serum of CP/CPPS patients ( 35 37 ). Here, we detected significantly higher serum IL-1β and TNF-α levels in EAP rats compared with normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the quantification of MIF in saliva has been increasing in various pathologies such as oral squamous cell carcinoma [31], in studies evaluating depressive symptoms [32], and in chronic pelvic pain syndrome [33], among others.…”
Section: Mif In Saliva and Serummentioning
confidence: 99%